THEOLOGICAL INTERPRETATION OF THE QURAN: AN ANALYSIS OF MUʿTAZILAH THOUGHT IN AL-KASHSHĀF BY AL-ZAMAKHSHARĪ - Jannah, Saadatul; Rahman, Yusuf (Peminat Ilmu Ushuluddin, 2023)
This article concludes that the interpretation of the Quran depends on the ideological and theological leanings of a mufassir. The findings support H-G. Gadamer’s claim about the mufassir’s pre-understanding, which is considered to have a close relationship with the interpretation result. This study shares the view of modernist Muslims, such as Naṣr Ḥāmid Abū Zayd, Farid Esack, Khaled Abou el-Faḍl, and feminist scholar Amina Wadud, that subjectivity in the interpretation of the Quran is inevitable because each mufassir lives in a different historical context and cultural reality. This article proves that the theological interpretation in al-Kashshāf is influenced by the Muʿtazilah principles of al-tawḥīd and al-ʿadl. The methodology of interpretation also portrays al-Zamakhsharī as an interpreter who has full authority in expressing his thoughts by using the question-and-answer method in his work. This article concludes that the interpretation of the Quran depends on the ideological and theological tendencies of the mufassir.